Penanggulangan Kemiskinan Melalui Pengembangan Pariwisata Berbasis Komunitas - Sunyoto Sunyoto; E Widayati (Sekolah Tinggi Pariwisata Sahid Surakarta, 2009)
Poverty is an urgent problem of the Indonesian people requires treatment measures and approaches that are systematic, integrated and comprehensive. The role of the tourism sector in improving the economy is relatively large. The purpose of this paper is to discuss on poverty and an effort to alleviate through the development of community-based tourism. Poverty is multidimensional, and involves some complex aspects. Therefore, the alleviation needs synergy and the concern of actors/stakeholders. There are three considered components are needed to formulatee strategies of poverty reduction through community-based tourism sector are the actors/stakeholders, institutional and pro poor policy, integrated and sustainable.